2018
DOI: 10.3390/ma11071070
|View full text |Cite
|
Sign up to set email alerts
|

The Preservation of Bone Cell Viability in a Human Femoral Head through a Perfusion Bioreactor

Abstract: Current methods for drug development and discovery involve pre-clinical analyses that are extremely expensive and time consuming. Animal models are not the best precedent to use, when comparing to human models as they are not synonymous with the human response, thus, alternative methods for drug development are needed. One of which could be the use of an ex vivo human organ where drugs could be tested and the effects of those drugs could be observed. Finding a viable human organ to use in these preliminary ex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Mechanical loading, static or cyclic, is important to maintain bone response [ 16 , 17 ]. Increased cell viability in bioreactor using medium perfusion through vasculature of femoral head was reported [ 18 ]. Some other models attempt to mimic bone remodeling in vitro [ 26 ], evaluate the viability of bone cells within 3D scaffolds [ 27 , 28 , 29 ] or used humanized mice bone model [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical loading, static or cyclic, is important to maintain bone response [ 16 , 17 ]. Increased cell viability in bioreactor using medium perfusion through vasculature of femoral head was reported [ 18 ]. Some other models attempt to mimic bone remodeling in vitro [ 26 ], evaluate the viability of bone cells within 3D scaffolds [ 27 , 28 , 29 ] or used humanized mice bone model [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The limitation of such organ models is the weak repopulation with the very few cells and, therefore, a need for additional seeding of osteoblasts, cultured in vitro [ 17 ]. The other limitation of reported ex vivo organ models is that bone tissue does not contain any vasculature and contain only the trabecular part of the bone [ 14 , 17 , 18 ]. Finally, up to now no studies reported an analysis of the outgrowth of bone cells onto implant surface using organ models.…”
Section: Introductionmentioning
confidence: 99%
“…Trabecular bone cores (Ø = 6-20 mm, height = 4-7 mm), obtained from femoral heads or tibia plateaus removed during replacement surgeries, demonstrated successful preservation of viability ex vivo, when cultured up to 4 weeks [14, 35, 43, 44•, 46, 80, 86, 87]. Notably, a recent study reported that an entire human femoral head could be kept viable for 12 h when culture medium was perfused through the remaining vasculature [24].…”
Section: Animal Bone Vs Human Bonementioning
confidence: 99%
“…But even if not considered replacement, the approach still contributes greatly to reduction and refinement by enabling multiple samples to be obtained for each animal sacrificed, reuse of material that might otherwise be wasted, and by refining the protocol to eliminate all experimentation on the animal while it is living. There is even scope to use human tissue by utilising waste from routine surgical procedures, such as femoral heads resected during hip arthroplasty ( Swarup et al, 2018 ; Styczynska-Soczka et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early research has demonstrated that ex vivo bone can grow and adapt to mechanical loading in a bioreactor setup ( Jones et al, 2003 ; Davies et al, 2006 ; David et al, 2008 ; Vivanco et al, 2013 ; Birmingham et al, 2015 ; Birmingham et al, 2016 ). More recent research has demonstrated material and cell transfer to an implant surface ( Dua et al, 2021 ; Zankovic et al, 2021 ) and that is possible to maintain viability in samples as large as human femoral heads ( Swarup et al, 2018 ; Styczynska-Soczka et al, 2021 ), but it is still not clear if the ex vivo bone can be used to explore the early stages of implant bone ingrowth into porous implants. Nor is it clear if the full remodelling pathways of bone are active.…”
Section: Introductionmentioning
confidence: 99%